Relasi Kehidupan Sosial pada Pembentukan Mental, Moral dan Akhlak dalam Perkembangan Kemampuan Anak - Baharuddin Baharuddin (Raheema, 2015)
The social life of the children could be understood from their daily life activities. Moreover, the closest matter is every attitude performing the mental maturity, moral acts, and the great akhlaq from children. Children are priceless treasures in parents’ life, thus, their success will depend on the education method used by family and the formal school. The indicator of parents’ success is seen from the ways they communicate with others.